A Review on Cluster Based Routing Protocols in Vehicular Adhoc Networks - Radhika, D; Bhuvaneswari, A (International Journal of Computer Sciences and Engineering, 2025)
Vehicular Adhoc Networks is an emerging technology for the communication of vehicles with the support of Intelligent Transportation Systems(ITS) to avoid fatal collisions and crashes on road and to ensure the road safety among the vehicles. The vehicles can be communicated through a wireless medium. Due to the rapid movement of vehicles and change in the topology leads to some message overheads with delays. Hence connectivity among the vehicles disappears and there is a need to identify an optimal path to be identified from source to destination for effective routing. A cluster will be formed to achieve a better link stability between the nodes and able to forward data to other members in case of any emergency situation. The safety message will be disseminated to other nodes in a limited short span of time. This paper gives a review on Vehicular Adhoc Networks(VANET) with its architecture, applications and various strategies which can be applied to form a cluster that yields high performance and evaluated with Quality of Service parameters.